2017
DOI: 10.1002/app.44814
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior of thermoplastic polymer nanocomposites containing graphene nanoplatelets

Abstract: Polypropylene (PP), acrylonitrile butadiene styrene (ABS), and thermoplastic polyurethane (TPU) nanocomposites filled with 5 wt % of two different kinds of commercially available graphene nanoplatelets (GNPs) were prepared. Composites materials were characterized in terms of thermal properties (thermal conductivity and thermal stability) in order to study the effect of different fillers within different thermoplastic matrices. The exfoliation process and the mechanical properties were also investigated. We cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 41 publications
4
30
0
Order By: Relevance
“…Zhang et al observed that the tensile strength increased after the incorporation of 4 wt % GNPs and that the tensile strength was higher when the nanocomposites had prepared by the die with shunt plates indicating that the high shear stress exfoliated the GNPs effectively to a thinner layer. A significant increase in the Young's modulus by graphene nanoplatelets from around 1.3 GPa to over 2.0 GPa was reported by Ahmad et al and an increase of more than 380% of the Young's modulus by Caradonna et al . Song et al observed an increase of tensile strength and Young's modulus in PP nanocomposites containing 1 wt% PP‐coated graphene, due to the homogeneous dispersion of graphene nanosheets and the effective load transfer from the matrix to graphene, because of their strong interfacial adhesion.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Zhang et al observed that the tensile strength increased after the incorporation of 4 wt % GNPs and that the tensile strength was higher when the nanocomposites had prepared by the die with shunt plates indicating that the high shear stress exfoliated the GNPs effectively to a thinner layer. A significant increase in the Young's modulus by graphene nanoplatelets from around 1.3 GPa to over 2.0 GPa was reported by Ahmad et al and an increase of more than 380% of the Young's modulus by Caradonna et al . Song et al observed an increase of tensile strength and Young's modulus in PP nanocomposites containing 1 wt% PP‐coated graphene, due to the homogeneous dispersion of graphene nanosheets and the effective load transfer from the matrix to graphene, because of their strong interfacial adhesion.…”
Section: Resultsmentioning
confidence: 88%
“…Liang et al [56] found that T 5% (corresponds to 5% loss) of PP composites with three types of GNPs, with lateral dimension <10, 0.5-20, 10-50 μm, increased, respectively, from 407.2 to 408.3, 411.1 and 413.6 C and the values of the T p increased, respectively, from 454.2 to 454.6, 455.7, and 457.3 C. Moreover, GNPs improved the activation energy of PP composites, and the activation energy increased with increasing the GNP lateral dimension due to the increase of mass barrier effect [56]. According to Caradonna et al [57], the addition of 5 wt% graphene nanoplatelets to PP led to an increase of > 20 and 11 C of T 5 % and T 50% respectively. Yuan et al [27] interpreted the delay of thermal degradation of pure PP by the high thermal conductivity of graphene that allows it to act as "efficient heat sink", which dissipates the external heat effectively and uniformly and thereby avoids the accumulation of heat.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Increased thermal stability is typical for polymer‐layered nanocomposites, usually attributed to heat and mass barrier effects of layered nanocompounds, which delayed heat and pyrolysis products diffusion . The thermal stability of SEBS/GE nanocomposites is represented by TGA.…”
Section: Resultsmentioning
confidence: 99%